Camping, climbing trees and marching to Parliament: spatial dimensions of environmental protest in New Zealand - O'Brien, Thomas (Taylor & Francis, 2015)
Environmental movements are key actors in challenging social and political constructions of the physical environment. A wide variety of protest campaigns have been undertaken in New Zealand, from local issues of pollution and road building through to national opposition to native forest logging and genetic engineering (GE). The aim of this paper is to examine the scales at which environmental protest in New Zealand have taken place and the impact upon the actions and durability of environmental campaigns. Through an analysis of a catalogue of protest events over the period 1997–2013, this paper describes patterns of actions, before examining the campaigns against GE field trials and mineral extraction in more detail. The findings point to the importance of cross-scale operations in enabling campaigns to capitalise on and respond to changes in the external environment including governance structures, resources and countermovement actors.
Keywords: genetic engineering; mining; protest event analysis; scale